The Principle Freedom of Contract In Share Repurchase Agreement (Repo) Transactions In The Capital Market - Dasuki Suhardini, Eni; Ramdania, Dini (Journal of Law, Politic and Humanities, 2024)
Transactions involving share repurchase agreements (repo) are one way for issuers to raise more money in order to boost the productivity of their businesses. The repo agreement, which is binding on both parties, is built on the idea of contract freedom. Even though the OJK has established repo transaction guidelines for financial service institutions, there are still some parties who don't carry out their commitments in accordance with what has been previously agreed upon in practice. The model for managing share repo transactions offers a sense of justice for shareholders, repo holders, and third parties. The obligations of repo holders in the event that the repo shares are sold to third parties. A normative-juridical approach is used to solve these issues, with the specification of analytical-descriptive research that examines facts and the implementation of repo transactions based on the provisions of the capital market laws and regulations. This research is supported by primary and secondary data obtained through document studies and interviews, which are then analyzed with kualitatif-juridical techniques. Based on the result of the research, it is possible to say that, although there are still some parties in practice who fail to uphold their obligations, the principle of freedom of contract has essentially been implemented for parties in share repo transactions between issuers in accordance with  the Civil Code and POJK; If the shares repoed to him are transferred to a third party before maturity, the share repo holder is subject to civil liability to the owner or a third party.